Ionic and Electronic Conductivities of Lithium Argyrodite Li6PS5Cl Electrolytes Prepared via Wet Milling and Post-Annealing - Lee, Jae Min; Park, Young Seon; Moon, Ji-Woong; Hwang, Haejin (Frontiers in Chemistry, 2021)
Lithium argyrodite Li6PS5Cl powders are synthesized from Li2S, P2S5, and LiCl via wet milling and post-annealing at 500 °C for 4 h. Organic solvents such as hexane, heptane, toluene, and xylene are used during the wet milling process. The phase evolution, powder morphology, and electrochemical properties of the wet-milled Li6PS5Cl powders and electrolytes are studied. Compared to dry milling, the processing time is significantly reduced via wet milling. The nature of the solvent does not affect the ionic conductivity significantly; however, the electronic conductivity changes noticeably. The study indicates that xylene and toluene can be used for the wet milling to synthesize Li6PS5Cl electrolyte powder with low electronic and comparable ionic conductivities. The all-solid-state cell with the xylene-processed Li6PS5Cl electrolyte exhibits the highest discharge capacity of 192.4 mAh·g-1 and a coulombic efficiency of 81.3% for the first discharge cycle.